ESTIMULACIÓN SENSORIAL Y SU INFLUENCIA EN EL PROCESO DE ENSEÑANZA- APRENDIZAJE EN EDUCACIÓN INICIAL II - RENDON LUNA GERALTY JAHILY (2024)
This research deals with sensory stimulation in the teaching-learning process of the “María Angelica Idrovo” initial education center in the province of Los Ríos, Vinces canton. Sensory stimulation and learning of students can be encouraged, supporting the development and teaching children through skills and activities that include the senses. It is given through a field method and is analyzed through surveys and bibliographies. The general problem of this research is how sensory stimulation affects the teaching-learning process in children in early education II. It is worth mentioning that sensory disorders may occur in children when sensory stimulation begins. That is why it is of great vitality that in the first years of an infant's life the process of sensory stimulation begins so that their skills can be developed and they can develop in society or in the environment that surrounds them. As possible results, we need the child to obtain better learning through sensory stimulation. Teachers at the educational institution must apply sensory stimulation to improve the memory, concentration, knowledge and skills of infants, thus benefiting their learning.